A new vision on the modelling of emerging infectious diseases - André TOTOHASINA; Bruce Masonova BEMENA; Daniel Rajaonasy FENO (Journal of Research and Multidisciplinary, 2021)
. Faced with the evolution of tools and method of mathematical modeling in epidemiology that we have for the treatment and prevention of the phenomenon of propagation of infectious diseases today, global warming plays a very important role in the genetic modification of microorganisms. This leads to the unsuitability of existing models such as the Susceptible, Exposed, Infected, Retired (SEIR) model proposed in the literature. The present paper proposes a Susceptible, Exposed, Precontaged, Infected, Retired (SEPIR) model adapted to the mechanism of diffusion of the new forms of the infectious diseases studied. This SEPIR model is specialized in cases where the infection spreads directly: first between precontagious individuals (asymptomatic) and susceptible individuals, second between infectious individuals (symptomatic) and susceptible individuals.